2006
DOI: 10.1111/j.1464-410x.2006.05871.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐exploration of the acute scrotum

Abstract: RESULTSThe median (range) age of the patients was 11.5 (2-15) years; 61 had two scrotal explorations and three were explored three times. Of the patients, 32 presented with right testicular pain, 31 had left pain, and one had bilateral testicular pain. In the second exploration, 56 of 64 had the contralateral testis explored, five had an ipsilateral exploration and three had bilateral exploration. Forty-eight of the 64 boys (70%) had torsion of the contralateral appendix testis at the second exploration, and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…1,5 However, there are only limited reports of early outcomes and re-presentation rates, particularly with comparison of conservative and operative management, with limited data on short-term morbidity associated with scrotal exploration. 3,[5][6][7][8][9][10] This study demonstrated a 10% re-presentation rate following initial management of the acute scrotum, with similar frequency of return in those managed conservatively and operatively at first presentation. Exploration rate on second presentation was notably higher in the subgroup of patients initially discharged without surgical intervention (71%).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…1,5 However, there are only limited reports of early outcomes and re-presentation rates, particularly with comparison of conservative and operative management, with limited data on short-term morbidity associated with scrotal exploration. 3,[5][6][7][8][9][10] This study demonstrated a 10% re-presentation rate following initial management of the acute scrotum, with similar frequency of return in those managed conservatively and operatively at first presentation. Exploration rate on second presentation was notably higher in the subgroup of patients initially discharged without surgical intervention (71%).…”
Section: Discussionsupporting
confidence: 53%
“…7 Similarly, in our centre, boys are just as likely to return with TA torsion on the contralateral side as they are to return with complications following surgical intervention (2.6% and 2.2%, respectively). This gives an incidence of return and operative intervention for contralateral TA of 2.6% (8/308); the number-neededto-treat with bilateral scrotal exploration and excision of non-torted TAs to prevent one re-presentation and exploration for a contralateral TA is therefore 39 (1/0.026).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In addition, clinical conditions such as testicular torsion and varicocele affect oxygen levels in the testis. Testicular torsion, or torsion of the spermatic cord, is a urologic medical emergency that primarily affects adolescent boys (Pentyala et al, 2001; Ben‐Meir et al, 2006; Ringdahl and Teague, 2006). Torsion can obstruct arterial and venous pathways, resulting in alterations in blood flow, ischemia, and hypoxia and causing acute or chronic cellular and molecular damage depending on the degree of cord rotation, duration of torsion, and subsequent tissue reperfusion that may occur following intervention (Pentyala et al, 2001; Ringdahl and Teague, 2006).…”
mentioning
confidence: 99%